Evaluation the behavior of seismic bracing connections based on clearance - Mojtaba Akrami (Iranian Society of Structrual Engineering (ISSE), 2018)
Today one of the most common systems for resisting lateral forces (wind and earthquake) is special concentrically braced frames (SCBF). Out of plane buckling in compression causes large inelastic flexural deformations in gusset plate. In order to supply the capacity of inelastic deformations in gusset plate, current design practice recommends a “2t” linear geometric offset to be used. Recent research has been done to improve the seismic behavior of connections for braced frames shown that the use of a clearance by elliptical pattern has better results than linear pattern clearance.In this paper using the finite element method, a one-story frame under cyclic loads and considering the nonlinear effects of material and geometric has been modeled and verified. The parameters that considered are effect of clearance (linear, elliptical and lack of clearance) at different angles and clearance in an elliptical pattern. The results of the samples, hysteresis curve, compressive and tensile resistance, as well as stress and strain showed that the clearance effect on tensile strength and compressive is between 2.86 to 13.5 percent for different angles of connected braces. Ductility in the case of lack of clearance between angles of 30 to 60 degrees reduced 30 to 60 percent relative to the elliptical clearance.